PENGARUH KEBIJAKAN HUTANG, KEBIJAKAN DIVIDEN, PROFITABILITAS, PERTUMBUHAN PENJUALAN DAN KESEMPATAN INVESTASI TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Vivi Apriliyanti; Hermi Hermi; Vinola Herawaty (Jurnal Magister Akuntansi Trisakti, 2019)
AbstractThe purpose of this study was to examine the influence of debt policy, dividend policy,profitability, sales growth and investment opportunity set on firm value with firm size as moderating variable in the manufacturing companies on the Indonesia Stock Exchange (IDX). The population used in this study is a company that is listed on the Indonesia Stock Exchange. The sample used in this study 128 companies with an observation period of 3 (three) years from 2016 to 2018. The method of determining the sample used in this study was the purposive sampling method. The data processing method used in this study is the causality test with multiple regression analysis using SPSS version 23. The independent variables in this study are Debt Policy, Dividend Policy, Profitability, Sales Growth and Investment Opportunity. The moderating variable in this study is Company Size. The dependent variable in this study is firm value. The results of this study indicate that Debt Policy has a positive effect on Firm’s Value, Dividend Policy does not effect on Firm Value, Profitability does not have a positive effect on Firm’s Value, Sales Growth does not effect on Firm’s Value, Investment Opportunity Set does not effect on Firm’s Value, Firm Size does not have a positive effect on Firm’s Value, Firm Size does not strengthen the realtionship between Debt Policy with Firm’s Value, Firm Size does not strengthen the realtionship between Dividend Policy with Firm’s Value, Firm Size does not strengthen the realtionship between Profitability with Firm’s Value, Firm Size does not strengthen the realtionship between Sales Growth with Firm’s Value, Firm Size does not strengthen the realtionship between Investment Opportunity Set with Firm’s Value.